Structural Analysis of Servant Leadership Promotes Employee Resilience and Organizational Citizenship Behavior among Employees - Eryc, Eryc; Palguna, Arya Irawan Putra; Sihombing, Dame Afrina; Anggiani, Sarfilianty (Universitas Nahdlatul Ulama Blitar, 2024)
This research aims to elucidate the relationship between servant leadership and organizational citizenship behavior mediated by employee resilience. The research employed a descriptive and verificative method with data analysis using Structural Equation Modeling. Primary data were collected through a survey of 398 employees from a state-owned bank in the Batam City region. The findings reveal that employee resilience has a positive and significant effect on the relationship between servant leadership and organizational citizenship behavior. The impact of servant leadership on organizational citizenship behavior is more dominant compared to the influence of employee resilience. However, this study has limitations. Organizational citizenship behavior is not solely influenced by servant leadership and employee resilience but is also affected by other factors, necessitating further research. The results of this study also suggest expanding the scope of the analytical unit to provide a broader contribution to the understanding of organizational citizenship behavior.